Claudin is an Immunohistochemical Changes Associated with Experimental Infection of White Mice with 0111 – of non – 0157 Shiga Toxin Producing Escherichia Coli - Khalil H. ALjeboori1 , Mukhald A. Ramadhan2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Immunohistochemical stain for the tissue sections prepared from experimental infection of mice with 0111 –of non 0157 of shiga toxin producing Escherichia coli .The immunohistochemical changes revealed that theshiga toxin produced by 0111 –STEC effect on epithelial tight Junction ,The IHC stain was directed to detectthe claudin ( the structural protein of tight Junction ) revealed absence of this protein in the paracellular siteswith discohesion of the epithelial cells in the intestine and endothelial cells in the brain blood vessels whichwas responsible for induction of diarrhea and nervous signs